2015
DOI: 10.5897/ijbc2015.0863
|View full text |Cite
|
Sign up to set email alerts
|

Inside the commons of ecotourism development in Ethiopia: Strategic communal empowerment or marginalization? Evidence from Wenchi community based ecotourism

Abstract: This paper examines the quest of empowerment and disempowerment, the way community based ecotourism created the marginalized community throughout its development phase in Ethiopia with evidence from Wenchi Ecotourism development. Descriptive research design was employed where as random sampling and purposive sampling techniques were used to determine the sample size. The sample representative for the study was 221 samples (196 for local community, 12 guides, 3 experts and 10 community representatives). Intervi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…Fast growing construction, weak formal institution, weak environmental protection law, socio-economic, cultural, legal and environmental and institutional problems are constraints for community based development in Ethiopia (Tesfaye, 2017a;Bantider et al, 2023). Teressa (2015) study revealed that there is lack of social network, norms and social trust in the Wenchi community based ecotourism. Instability, terrorism in the Horn Africa, drought and famine incompatibility of interest among stakeholders, challenges related to cultural sustainability, lack of security and safety were the main challenges for community based ecotourism development (Asmare, 2016;Abdel-Latif and Mokkadem, 2016;Shaw, 2016;Gottert, 2016;Wondirad et al, 2020).…”
Section: Other Challengesmentioning
confidence: 99%
“…Fast growing construction, weak formal institution, weak environmental protection law, socio-economic, cultural, legal and environmental and institutional problems are constraints for community based development in Ethiopia (Tesfaye, 2017a;Bantider et al, 2023). Teressa (2015) study revealed that there is lack of social network, norms and social trust in the Wenchi community based ecotourism. Instability, terrorism in the Horn Africa, drought and famine incompatibility of interest among stakeholders, challenges related to cultural sustainability, lack of security and safety were the main challenges for community based ecotourism development (Asmare, 2016;Abdel-Latif and Mokkadem, 2016;Shaw, 2016;Gottert, 2016;Wondirad et al, 2020).…”
Section: Other Challengesmentioning
confidence: 99%
“…In Ethiopia, tourism has a vital role to play in the development of the nation and continues to grow continuously in recent years [19]. In 2017, tourism's contribution to GDP represents 6.8% of total GDP, 6.1% of total employment, and 2.4% of total investment, respectively [8].…”
Section: Community-based Ecotourism In Ethiopiamentioning
confidence: 99%
“…In 2017, tourism's contribution to GDP represents 6.8% of total GDP, 6.1% of total employment, and 2.4% of total investment, respectively [8]. Tourism is therefore becoming one of the major economic activities in Ethiopia [19].…”
Section: Community-based Ecotourism In Ethiopiamentioning
confidence: 99%
See 1 more Smart Citation